Decagram-Scale Synthesis of N -{2-[4-(β- d -Glucopyranosyloxy)-2-methylphenyl]-1,1-dimethyl-2-oxoethyl}-3-methylthiophene-2-carboxamide (GPTC), a Metabolite of the Fungicide Isofetamid - Jang, Hongjun; Kwak, Soo Yeon; Kim, Young Hoon; Han, Jae Hyuk; Park, Youngjik; Baek, Seung Hoon; Lee, Dongjoo; Kim, Hyoungsu (Synlett, 2023)
A decagram-scale synthesis of N-{2-[4-(?-D-glucopyranosyloxy)-2-methylphenyl]-1,1-dimethyl-2-oxoethyl}-3-methylthiophene-2- carboxamide (GPTC), a metabolite of the fungicide isofetamid, has been achieved in a highly straightforward manner from the known compound 1-(4-hydroxy-2-methylphenyl)-2-methylpropan-1-one in eight steps with a 20% overall yield to provide a standard certified reference material for residue analysis in food.
Keywords: certified reference materials; GPTC; isofetamid; large-scale synthesis